Implications of silver nanoparticles for H. pylori infection: modulation of CagA function and signaling - Hochvaldova, Lucie; Posselt, Gernot; Wessler, Silja; Kvítek, Libor; Panáček, Aleš (Frontiers in Cellular and Infection Microbiology, 2024)
Helicobacter pylori infection poses a significant health burden worldwide, and its virulence factor CagA plays a pivotal role in its pathogenesis. In this study, the interaction between H. pylori-infected AGS cells and silver nanoparticles (AgNPs) was investigated, with a focus on the modulation of CagAmediated responses. Both, the dose-dependent efficacy against H. pylori and the impact of the nanoparticles on AGS cells were elucidated. AGS cells infected with H. pylori displayed dramatic morphological changes, characterized by elongation and a migratory phenotype, attributed to CagA activity. Preincubation of H. pylori with AgNPs affected these morphological changes in a concentration-dependent manner, suggesting a correlation between AgNPs concentration and CagA function. Our study highlights the nuanced interplay between host-pathogen interactions and the therapeutic potential of AgNPs in combating H. pylori infection and offers valuable insights into the multifaceted dynamics of CagA-mediated responses.